Undernourishment in North and sub-Saharan Africa - Mayssa, Hedhli; Leila, Nasri; Fatma, MRAD (Journal of Ecohumanism, 2024)
Undernourishment has continued to occur globally in recent years; the spread of this phenomenon shows that inequalities, between and within countries, are increasing. After a good period of stability since 2015, the prevalence of undernourishment (PoU) dropped from 8.0 percent to 9.3 percent between 2019 and 2020, then increased at a less sustained rate in 2021, rising to 9.8 percent. The causal factors to eliminate or reduce its severity differ from one country to another. The causes of hunger in the countries of North Africa are: independence from food imports of primary products, loss of marine biodiversity, climate change (projected change in warm periods) and poverty in terms of available water resources cause while malnutrition or moderate food insecurity comes down to the lack of commitments in international conventions on the environment and the respect and enforcement of the law against trafficking in natural resources. The causal variables of these two phenomena in the countries of sub-Saharan Africa are identical.The great pressure that the population exerts on their environment and the enormous consumption of resources without having them protected, also the total deterioration of the agricultural sector and the Emigration to urban areas has greatly worsened the situation of hunger and malnutrition in these countries. The projects implemented to resolve these issues must be designed according to the causes identified in each country. In general, the reorientation of public support must currently be provided to strengthen the primary sector (food and agriculture), by implementing complementary policies relating to agri-food systems, promoting healthy food environments and providing consumers with the means to adopt a healthy diet.